HCI International 2011 Posters extended abstracts international conference, HCI International 2011, Orlando, FL, USA, July 9-14, 2011, proceedings. Part I - Stephanidis, Constantine (Communications in Computer and Information Science, 2011)
This two-volume set CCIS 173 and CCIS 174 constitutes the extended abstracts of the posters presented during the 14th International Conference on Human-Computer Interaction, HCII 2011, held in Orlando, FL, USA in July 2011, jointly with 12 other thematically similar conferences. A total of 4039 contributions was submitted to HCII 2011, of which 232 poster papers were carefully reviewed and selected for presentation as extended abstracts in the two volumes.